Penggunaan Keong Bakau Telescopium sp (Gastropoda: Potamididae) dan Siput Bakau Cerithidea sp (Gastropoda: Potamididae) Sebagai Biofilter terhadap Limbah Budidaya Ikan Bandeng (Chanos chanos) - Munawar Khalil; Riri Ezraneti; Jannatiah Jannatiah; Siti Hajar (Journal Omni-Akuatika, 2016)
Mangrove snail Telescopium sp and Cerithidea sp are natural biofilter that able used to manage the changes in water quality caused by the culture sewage. This research aimed to analyze the utilization of Telescopium sp and Cerithidea sp as natural biofilter for re-improving water quality level from culture sewage in the laboratory scale. The outcome of this study was expected to be valuable information that mangrove gastropods not only as pests in mariculture ponds, but also able to use as natural biofilter in pond sewage management for recovering water quality level. This research was conducted from April to July 2016 in Hatchery and Aquaculture Technology Laboratory, Aquaculture Department, Agriculture Faculty, Malikussaleh University. Descriptive and quantitative methods used in this research including two treatment and three replications. Water quality such as turbidity, temperature, ammonia, nitrate, nitrite, orthophosphate, pH and dissolved oxygen measured periodically as research parameters. The result showed that the utilization of mangrove gastropod Telescopium sp and Cerithidea sp as natural biofilter was able to re-improving the water quality value such as pH, ammonia, nitrat, nitrit, orthophosphate and turbidity to the normal level. Meanwhile, the utilization of mangrove gastropods as natural biofilter does not gave any significant changes in the value of temperature, salinity and dissolved oxygen. Cerithidea sp also has better performance to reduce the water nutrient level in culture sewage compared than Telescopium sp. Keyword: mangrove gastropod, biofiltration, water quality, culture sewage